Human immunodeficiency virus-related Epstein-Barr virus-associated smooth muscle tumours: South African experience from Chris Hani Baragwanath Academic Hospital. Issue 4 (2nd October 2017) - Pather, Sugeshnee; Wainwright, Rosalind D.; Sahid, Faieza; Mashele, Thembi; van den Berg, Eunice J.; Mohanlal, Reena D.
Abstract: Background: Despite the rampant human immunodeficiency (HIV) epidemic in Africa, there is a paucity of published data of HIV-related Epstein-Barr virus-associated smooth muscle tumours (EBV-SMT) from Africa. Methods: We embarked on retrospective documentation of the clinicopathological features of confirmed HIV-related EBV-SMT over a 5-year time frame at the largest hospital in Africa. All haematoxylin and eosin stained tissue sections, immunohistochemistry and EBV in situ hybridisation (ISH) investigations were reviewed in conjunction with clinical data. Results: Fourteen ( n = 14) EBV-SMT were confirmed in 13 patients (age range: 10–53 years). Five paediatric patients and a predominance of females (70%) were evident in this series. All patients were HIV seropositive and CD4 counts ranged from 1 to 1331 cells/ul (median 355 cells/ul; mean 442 cells/ul). Tumour-associated pain was a common symptom in the paediatric age group, while neurological symptoms were frequent in the adults due to paraspinal cervicothoracic involvement. Unusual topography, multifocality ( n  = 5) and smooth muscle morphology in association with round cell features ( n  = 3) were evident. Immunoexpression of desmin ( n  = 12), SMA ( n  = 12) and h-Caldesmon ( n  = 8) were consistent findings and positive EBV ISH nuclear signaling was demonstrated within all of these tumours. Treatment included antiretroviral therapy, surgical resection, radiation and/or palliative therapy. Conclusion: HIV-associated EBV-SMT are rare tumours that may develop in paediatric or adult patients. A female predominance and multifocal topographic involvement may be evident. AIDS-related co-morbidities are likely to contribute to mortality; and, when these tumours occur in paraspinal regions, debilitating neurological morbidity may manifest.